Willingness to get vaccinated against Ebola: A mapping of Guinean people positions - Kpanake, Lonzozou (Hum Vaccin Immunother, 2018)
Objective: To map the different personal positions of Guinean people regarding vaccination against Ebola. Methods: From January to April 2016, 304 adults in Guinea were presented with 48 vignettes depicting situations in which getting vaccinated would be possible. These situations varied as a function of the constructs of health-protective behavior theories. The participants indicated the likelihood they would get vaccinated in each case. Results: Seven qualitatively different positions were found: Always Vaccinate (38%), Never Vaccinate (25%), Hesitant (19%), Depends on Cost Only (7%), Depends on Neighbors' Attitude and Cost (5%), Mainly Depends on Risk (4%), and Mistrust of Cheap Vaccines (2%). Conclusion: The diversity of Guinean people's positions implies that Ebola vaccination campaigns in Guinea, and probably in other sub-Saharan African countries, must not be “one size fits all,” but must be multifaceted and tailored in design and implementation to match the diversity of these people's needs and views.